2003
DOI: 10.1144/1467-787302-045
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater flow in playa lake environments: impact on gold and pathfinder element distributions in groundwaters surrounding mesothermal gold deposits, St. Ives area, Eastern Goldfields, Western Australia

Abstract: Geochemical sampling of groundwater may be an effective tool in exploring for Au deposits in areas of transported overburden. However, to use hydrogeochemistry effectively, we need to understand which elements are useful pathfinders and how their distribution patterns are affected by groundwater flow and geochemistry, especially in areas that have hypersaline groundwater. A hydrogeochemical survey was completed over the strongly Au-endowed St. Ives area of the Eastern Goldfields of Western Australia. Extensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…This is much higher than commonly detected in groundwater associated with gold mineralization (e.g., up to 52 ppt; Gray, 2001;Carey et al, 2003), although up to approximately 40 ppb has been detected in groundwater from drill holes within pits of gold mines in the Yilgarn of Western Australia (the high values may be an artifact of the mining activity and consequent release of high levels of thiosulfate; Gray, 2001). The implications of this are that these groundwaters are well undersaturated with respect to native gold, even in areas of gold mineralization, and/or that the thermodynamic properties for native gold solubility reactions at low temperature overestimate the solubility and need to be refined.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…This is much higher than commonly detected in groundwater associated with gold mineralization (e.g., up to 52 ppt; Gray, 2001;Carey et al, 2003), although up to approximately 40 ppb has been detected in groundwater from drill holes within pits of gold mines in the Yilgarn of Western Australia (the high values may be an artifact of the mining activity and consequent release of high levels of thiosulfate; Gray, 2001). The implications of this are that these groundwaters are well undersaturated with respect to native gold, even in areas of gold mineralization, and/or that the thermodynamic properties for native gold solubility reactions at low temperature overestimate the solubility and need to be refined.…”
Section: Discussionmentioning
confidence: 79%
“…The presence of [AuCl 4 ] À and other high-order gold halide complexes has potential implications for the formation of secondary supergene deposits, as the solubility of native gold decreases markedly with decreasing halide concentration (Fig. 13), important, for example, at the margins of playa systems where brines mix with less saline waters (e.g., Lake Lefroy in Western Australia;Carey et al, 2003). For many oxidized, saline waters and brines, [AuCl 4 ] À is likely to be the predominant gold complex, but for Cl/Br ratios such as in the Smackover Formation and seawater, mixed Au(III) bromide-chloride complexes are likely to predominate at acidic pH (e.g., less than 6; Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the occurrence of soluble gold must be considered dynamic since precipitation of elemental gold and formation of gold (III) chloride complexes can occur contemporaneously. It is important to note that gold concentrations have been measured in natural saline waters (Koide et al 1988) and in surficial, hypersaline groundwater located near mesothermal gold deposits (Carey et al 2003).…”
mentioning
confidence: 99%
“…Understanding these biospheric contributions to gold immobilization has relevance because they provide information about fundamental processes that need to be incorporated into geochemical exploration programmes, creating additional means of vectoring geochemistry data to discover buried gold deposits and near-surface deposits containing gold. The Eastern Goldfields of Western Australia is one example of such an environment where soluble gold is transported as gold (III) chloride within groundwater systems and immobilized within calcrete (Carey et al 2003). Studies by Lintern et al (2009Lintern et al ( , 2011 indicated that, in semi-arid regions, soluble gold is derived from the leaching of underlying primary sources and transported to surficial environments.…”
mentioning
confidence: 99%